2007
DOI: 10.1002/jbm.b.30831
|View full text |Cite
|
Sign up to set email alerts
|

Repair of the dura mater with processed collagen devices

Abstract: The three dural substitutes tested were found to be safe and effective in healing surgically created defects in the dura mater. Although each of these dura substitutes are composed of collagen, differences in the collagen source and processing influenced device physicomechanical properties, porosity, and the nativity of the collagen polymer. These measured differences influenced device intraoperative handling and installation as well as the post-operative biological response, where differences in device resorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
75
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(79 citation statements)
references
References 22 publications
1
75
0
3
Order By: Relevance
“…To the best of our knowledge, previous animal studies [7, 8, 17, 19] did not investigate adhesions between semisynthetic collagen onlay grafts and lesioned cortex. Adhesions between graft and cortex are of significance in clinical use, since they might act as an epileptic focus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, previous animal studies [7, 8, 17, 19] did not investigate adhesions between semisynthetic collagen onlay grafts and lesioned cortex. Adhesions between graft and cortex are of significance in clinical use, since they might act as an epileptic focus.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to previous animal studies for dural repair [1, 5, 7, 8, 10, 1315, 1719], in the present study, a dural defect and a cortical lesion were created to study the adhesion of devices to the dura, their subsequent tissue integration, and potential adhesion and scar formation with the underlying lesioned cortex. Properties of the dural substitutes regarding intraoperative handling and workability, initial watertightness of the dural reconstruction during surgery, biocompatabiliy, tissue integration and formation of adhesion to the intact or lesioned cortex were analysed at 1 and 6 months after the surgery.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12] However, the risk of disease transmission from allografts or animal-derived xenografts raises serious concerns. 2,5 Recent efforts have also been paid in bioresorbable synthetic polymer membranes as they are stronger, more suturable and lower in cost than collagen matrices. Poly(lactic acid) (PLA), polyglycolic acid (PGA) and poly("-caprolactone) (PCL) as well as copolymers of them are typical examples of FDA approved, semicrystalline polyesters that may degrade via hydrolysis of their ester linkages under physiological conditions with nontoxic degradation products.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, gels placed in living tissues are remodeled over time by enzymes such as matrix metallo-proteases, enhancing the potential for integration of implants with surrounding tissue. Collagen is also used clinically in neurosurgery as a replacement for the outer meningeal membrane of the brain (Zerris et al, 2007) and has shown efficacy for the treatment of burns and slow healing skin wounds (Falanga & Sabolinski, 1999) and in reparation of damaged vocal cords (Luu et al, 2007; Kimura et al, 2010). …”
Section: Introductionmentioning
confidence: 99%